Use of straw mushrooms (Volvariella volvacea) for the enhancement of physicochemical, nutritional and sensory profiles of Cantonese sausages. (December 2018) - Wang, Xuping; Zhou, Pengfei; Cheng, Jingrong; Chen, Zhiyi; Liu, Xueming
Abstract: The aim of this work was to evaluate the quality and sensory properties of Cantonese sausages incorporated with dried straw mushrooms. Five types of sausage with the addition of 0%, 1%, 2%, 3%, and 4% straw mushrooms were prepared, and their physicochemical traits and sensory acceptance were investigated. The results showed that incorporation of straw mushrooms improved the physical properties, significantly decreased peroxide value, increased the amount of amino acids and volatile compounds, and introduced new volatiles (aldehyde and ester compounds) to Cantonese sausages. Compared to sausages without addition of straw mushrooms, the amount of essential amino acids increased 8-fold, the P/S ratio of fatty acid increased to 0.46 similar to the recommended nutritional value, and the lipid peroxide value reduced 10-fold in Cantonese sausages with addition of 4% straw mushrooms. These results indicate that incorporation of straw mushrooms could be an efficient way to obtain nutritional and healthy Cantonese sausages. Highlights: Effect of straw mushroom on physiochemical and sensorial properties were evaluated. The straw mushroom improved the flavor and overall quality of Cantonese sausages. The peroxide value was reduced in the sausages incorporated with straw mushroom. The straw mushroom enhanced the amount of amino acids and volatile compounds in Cantonese sausage. Cantonese sausage containing 2% of straw mushroom scored best for general acceptability.